Relationship Between Teachers' Emotional, Social and Spiritual Intelligences and Their Classroom Discipline Strategies in Selected Secondary Schools in Selangor, Malaysia - Yahyazadeh, Soleiman Jeloudar (2011)
The purpose of this study was to investigate the relationship between teachers’emotional, social and spiritual intelligences and their classroom discipline strategies in secondary schools. The classroom discipline strategies explored are punishment, discussion,recognition, aggression, involvement, and hinting. The study also investigated possible relationships between teachers’ classroom discipline strategies as perceived by teachers and students. Thus, the descriptive correlational methodology was adopted for this study. Discipline problems are rampant throughout Malaysia and Selangor is no exception. Thus, choice of Selangor and a randomly chosen district in Selangor can describe discipline problems in a typical urban state. A total of 203 teachers and 2147 students in five areas in Selangor participated in this study. They were selected based on random sampling from 13 schools. Data were collected in a survey and analyzed using both descriptive and inferential statistics. The teachers were required to answer questionnaires for measurements of their emotional, social and spiritual intelligences using the well established Emotional Competencies Inventory (ECI), Tromsø Social Intelligence Scale (TSIS), and Integrated Spiritual Intelligence Scale (ISIS) respectively. The teachers were also required to answer a questionnaire that reveals their perception of their classroom discipline strategies. The students had responded to another version of the questionnaire that showed their perception of the teachers’ classroom discipline strategies. In this study, the independent variables are emotional, social and spiritual intelligences and the dependent variables are classroom discipline strategies. One another level, seven demographic variables; gender, age,religion, race, teaching experience, academic qualifications, and level taught are independent variables for the dependent variables; emotional, social and spiritual intelligences. This research revealed that there was significant relationship between emotional, social and spiritual intelligences and demographic variables such as age, ethnicity, religion,and teaching experience but no significant relationship was established with gender and levels taught. In terms of relationship between the dependent and independent variables,the results indicated that there was a significant and positive relationship between emotional, social and spiritual intelligences and four strategies of classroom discipline (discussion, recognition or reward and hinting), but negative relationship was established toward aggression and punishment. Relationship between teachers’ social and spiritual intelligence there was no significant relationship between teachers’ emotional intelligence and punishment. This study proceeded with a multivariate analysis of variance (MANOVA). MANOVA has clearly indicated that teachers of different levels of emotional, social and spiritual intelligence significantly differ in their usage of both positive disciplinary strategies (discussion, recognition, hinting and involvement) and negative ones (punishment and aggression).with punishment was significant but negative. In addition,